(untitled) (American Journal of Society and Law, 2022)
The study was designed to determine the adversity quotient and degree of stress of the police officers in the Province of Northern Samar. It was conducted among 288 police officers in the Province of Northern Samar. A descriptive- research approach was utilized to conduct the study. The results found that police officers in Northern Samar are dominated by males aged 25 to 30 years old, college graduates whose rank or position is patrolman/woman, served for 6 years or shorter and attended 0 to 3 relevant pieces of training on mental health. The adversity quotient® of the police officers in Northern Samar is low. The adversity quotient of the respondents differed across age, sex, educational attainment, rank or position and the number of years in service and experienced moderate stress on both operational and organizational stress. Likewise, their degree of stress differs in terms of age, sex, educational attainment, rank/position, number of years in service, and, the number of training attended. The operational stress of respondents is significantly related to age, number of years in service, and the number of relevant trainings attended whereas, profile such as sex, educational attainment and rank/position showed no relationships. In contrast, their occupational stress is significantly related to age, number of years in service. The number of relevant trainings attended however, sex educational attainment and the rank or position showed no relationship at all. Therefore, an implementation of crisis intervention program is needed for a balanced mental health condition of the police officers in Northern Samar.